Dinamika Populasi Anakan Pohon Klimaks Calophyllum soulattri Burm dan Swintonia schwenkii T.&B Di Hutan Bukit Pinang-Pinang - Sari Fatul Husna; Erizal Mukhtar; Chairul Mahmud (Jurnal Biologi Universitas Andalas, 2015)
A study on population dynamics of Calophyllum soulattri Burm and Swintonia schwenkii T.&B in Pinang-Pinang rain forest have been carried out from September 2012 to Februari 2013 by using descriptive method. Data were collected after 23 years of demographic data available. We found that the highest seedling mortality of Calophyllum soulattri was at the height class of 11-30 cm (9.4 %) and the lowest was at the height class of 71- 80 cm (3.4 %). The heighest seedling mortality of Swintonia schwenkii was  at the height class of 11-20 cm (10.3 %) and the lowest was at height class 51-60 cm (2.9 %). Relative height growth rate of Calophyllum soulattri seedling was at the height class of 21-30 cm (0.38 cm/cm/yr). Whereas relative height growth rate of Swintonia schwenkii seedling was at the height class of 31-40 cm (0.21 cm/cm/yr). Keywords: dynamics population, Calophyllum soulattri, Swintonia schwenkii,mortality, relative high growth rate.